English phraseological units of speech behavior reflecting household realities - Turlybekova, I.A.; Nurkenova, S.S. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article considers the role of phraseologisms with the meaning of speech behavior in the English language. The aim of the study is the identification of the English phraseologisms with the meaning of speech behavior defining the phraseologisms directly related to household realities. In the article, the English phraseologisms denoting speech behavior are distinguished from other phraseologisms and among them the phraseological units reflecting household realities are chosen in order to reveal their meaning. Phraseologisms trace the connection of the language with culture and they are characterized by various historical facts. All events in the life of the nation obtain their reflection in the vocabulary. Phraseological units of speech behavior reflecting household realities, selected from phraseological dictionaries, are analyzed to identify the most striking examples of the household realities. In the course of our research, the methods of continuous sampling were used for the selection of language material and also the methods of description, quantitative calculation. The analysis of the linguistic material showed that the most frequent among the household realities of the English language were phraseological units denoting the names of food and drinks. This is followed by the phraseological units describing dwellings and constructions and the phraseological units depicting clothes and shoes. Significantly less common phraseological units turned out to be phraseological units denoting vehicles.
Тұрмыстық реалияларды бейнелейтін ағылшын тіліндегі сөйлеу тәртібінің фразеологизмдері
Английские фразеологизмы речевого поведения, отражающие бытовые реалии
Keywords: phraseology; realities; culture; non-equivalent vocabulary; classification of realities; cultural inside; speech behavior; local coloring